2013
DOI: 10.2175/106143012x13560205144371
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Energy Use and Greenhouse Gas Emission Analysis for a Water Resource Recovery Facility in India

Abstract: This paper quantifies life cycle energy use and greenhouse gas (GHG) emissions associated with water resource recovery facilities (WRRFs) in India versus water quality improvements achieved from infrastructure investments. A first such analysis is conducted using operating data for a WRRF, which employs upflow anaerobic sludge blanket (UASB) reactors and oxidation. On-site operations energy use, process GHG emissions, and embodied energy in infrastructure were quantified. The analysis showed energy use and GHG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…WWTP Parameters: Like many WWTPs in India, N-WWTP uses upflow anaerobic sludge blanket (UASB) technology followed by oxidation and polishing ponds for secondary treatment. Some WWTPs in India use aerobic treatment processes like activated sludge (Miller et al 2013), which are thought to use more energy (USEPA and NREL 1995) and emit fewer GHGs (Heffernan et al 2012) than anaerobic treatment processes; however the differences in the effectiveness of these treatments in India are not wellquantified and are beyond the scope of this single case study. In this paper, the additional impacts of using treated wastewater in urban agriculture and/or releasing it to a stream are evaluated yielding an LCA of the combination of wastewater treatment and reuse in agriculture; biosolids are not included because they remained on-site at the time of the field study.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…WWTP Parameters: Like many WWTPs in India, N-WWTP uses upflow anaerobic sludge blanket (UASB) technology followed by oxidation and polishing ponds for secondary treatment. Some WWTPs in India use aerobic treatment processes like activated sludge (Miller et al 2013), which are thought to use more energy (USEPA and NREL 1995) and emit fewer GHGs (Heffernan et al 2012) than anaerobic treatment processes; however the differences in the effectiveness of these treatments in India are not wellquantified and are beyond the scope of this single case study. In this paper, the additional impacts of using treated wastewater in urban agriculture and/or releasing it to a stream are evaluated yielding an LCA of the combination of wastewater treatment and reuse in agriculture; biosolids are not included because they remained on-site at the time of the field study.…”
Section: Site Descriptionmentioning
confidence: 99%
“…12 (2017) 075005 season in online supplementary table S1 available at stacks.iop.org/ERL/12/075005/mmedia.The indicator microorganisms of interest in soil, water, and on the crop were Escherichia coli (E. coli; a coliform indicator) and nematode ova or eggs (roundworm Ascaris lumbricoides (Ascaris); and hookworm: no distinction was made between Old World, Ancylostoma duodenale, and New World Necator americanus hookworm). E. coli and nematode eggs are commonly used as indicators of wastewater contamination and associated health risks(Cifuentes 1998, Mara et al 2007, Ensink et al 2008. Parameters, such as macronutrients, organics, microorganisms, and physical characteristics, were measured in the irrigation water, soil, soil water, and vegetable matter for each plot, and used in calculations and comparisons across plots; tests were carried out primarily at the International Crop Research Institute for the Semi-Arid Tropics (ICRISAT) labs (methods detailed in table S1).…”
mentioning
confidence: 99%
“…Life cycle energy use and GHG emissions associated with water resource recovery facilities (WRRFs) in India were assessed by Miller-Robbie et al (2013). It was found that average WRRF-associated GHG emissions were lower than the expected value for untreated wastewater if released to the river.…”
Section: Ghg Emissions From Wwtpsmentioning
confidence: 99%
“…Recently, studies have shown that it is indeed possible to operate a wastewater treatment plant to produce effluent of time-varying quality (Neto et al, 2021). Moreover, a new approach has been proposed to achieve even better recovery of nutrients, and transform treatment plants into wastewater resources recovery facilities (Aichouche, 2021;Miller-Robbie et al, 2013). It is still a challenge to manage treatment systems to retain nutrients while guaranteeing a water free of pathogens and micro-pollutants, but technologies are being developed, such as membrane filtration systems, precisely allowing to deliver safe water (Judd, 2010).…”
Section: Introductionmentioning
confidence: 99%